How to find the general solution of an equation of the form tan θ = tan ∝?
Prove that the general solution of tan θ = tan ∝ is given by θ = nπ +∝, n ∈ Z.
Solution:
We have,
tan θ = tan ∝
⇒ sin θ/cos θ  sin ∝/cos ∝ = 0
⇒ (sin θ cos ∝  cos θ sin ∝)/cos θ cos ∝ = 0
⇒ sin (θ  ∝)/cos θ cos ∝ = 0
⇒ sin (θ  ∝) = 0
⇒ sin (θ  ∝) = 0
⇒ (θ  ∝) = nπ, where n ∈ Z (i.e., n = 0, ± 1, ± 2, ± 3,…….), [Since we know that the θ = nπ, n ∈ Z is the general solution of the given equation sin θ = 0]
⇒ θ = nπ + ∝, where n ∈ Z (i.e., n = 0, ± 1, ± 2, ± 3,…….)
Hence, the general solution of tan θ = tan ∝ is θ = nπ + ∝, where n ∈ Z (i.e., n = 0, ± 1, ± 2, ± 3,…….)
Note: The equation cot θ = cot ∝ is equivalent to tan θ = tan ∝ (since, cot θ = 1/tan θ and cot ∝ = 1/tan ∝). Thus, cot θ = cot ∝ and tan θ = tan ∝ have the same general solution.
Hence, the general solution of cot θ = cot ∝ is θ = nπ + ∝, where n ∈ Z (i.e., n = 0, ± 1, ± 2, ± 3,…….)
1. Solve the trigonometric equation tan θ = \(\frac{1}{√3}\)
Solution:
tan θ = \(\frac{1}{√3}\)
⇒ tan θ = tan \(\frac{π}{6}\)
⇒ θ = nπ + \(\frac{π}{6}\), where n ∈ Z (i.e., n = 0, ± 1, ± 2, ± 3,…….), [Since, we know that the general solution of tan θ = tan ∝ is θ = nπ + ∝, where n ∈ Z (i.e., n = 0, ± 1, ± 2, ± 3,…….)]
2. What is the general solution of the trigonometric equation tan x + tan 2x + tan x tan 2x = 1?
Solution:
tan x + tan 2x + tan x tan 2x = 1
tan x + tan 2x = 1  tan x tan 2x
\(\frac{tan x + tan 2x}{1  tan x tan 2x}\) = 1
tan 3x = 1
tan 3x = tan \(\frac{π}{4}\)
3x = nπ + \(\frac{π}{4}\), where n = 0, ± 1, ± 2, ± 3,…….
x = \(\frac{nπ}{3}\) + \(\frac{π}{12}\), where n = 0, ± 1, ± 2, ± 3,…….
Therefore, the general solution of the trigonometric equation tan x + tan 2x + tan x tan 2x = 1 is x = \(\frac{nπ}{3}\) + \(\frac{π}{12}\), where n = 0, ± 1, ± 2, ± 3,…….
3. Solve the trigonometric equation tan 2θ = √3
Solution:
tan 2θ = √3
⇒ tan 2θ = tan \(\frac{π}{3}\)
⇒ 2θ = nπ + \(\frac{π}{3}\), where n ∈ Z (i.e., n = 0, ± 1, ± 2, ± 3,…….), [Since, we know that the general solution of tan θ = tan ∝ is θ = nπ + ∝, where n ∈ Z (i.e., n = 0, ± 1, ± 2, ± 3,…….)]
⇒ θ = \(\frac{nπ}{2}\) + \(\frac{π}{6}\), where n ∈ Z (i.e., n = 0, ± 1, ± 2, ± 3,…….)
Hence, the general solution of tan 2θ = √3 is θ = \(\frac{nπ}{2}\) + \(\frac{π}{6}\), where n ∈ Z (i.e., n = 0, ± 1, ± 2, ± 3,…….)
4. Find the general solution of the trigonometric equation 2 tan x  cot x + 1 = 0
Solution:
2 tan x  cot x + 1 = 0
⇒ 2 tan x  \(\frac{1}{tan x }\) + 1 = 0
⇒ 2 tan\(^{2}\) x + tan x  1 = 0
⇒ 2 tan\(^{2}\) x + 2tan x  tan x  1 = 0
⇒ 2 tan x(tan x + 1)  1(tan x + 1) = 0
⇒ (tan x + 1)(2 tan x  1) = 0
⇒ either tan x + 1 = or, 2 tan x  1 = 0
⇒ tan x = 1 or, tan x = \(\frac{1}{2}\)
⇒ tan x = (\(\frac{π}{4}\)) or, tan x = tan α, where tan α = \(\frac{1}{2}\)
⇒ x = nπ + (\(\frac{π}{4}\)) or, x = mπ + α, where tan α = \(\frac{1}{2}\) and m = 0, ± 1, ± 2, ± 3,…….
⇒ x = nπ  (\(\frac{π}{4}\)) or, x = mπ + α, where tan α = \(\frac{1}{2}\) and m = 0, ± 1, ± 2, ± 3,…….
Therefore the solution of the trigonometric equation 2 tan x  cot x + 1 = 0 are x = nπ  (\(\frac{π}{4}\)) and x = mπ + α, where tan α = \(\frac{1}{2}\) and m = 0, ± 1, ± 2, ± 3,…….
5. Solve the trigonometric equation tan 3θ + 1 = 0
Solution:
tan 3θ + 1 = 0
tan 3θ =  1
⇒ tan 3θ = tan (\(\frac{π}{4}\))
⇒ 3θ = nπ + (\(\frac{π}{4}\)), where n ∈ Z (i.e., n = 0, ± 1, ± 2, ± 3,…….), [Since, we know that the general solution of tan θ = tan ∝ is θ = nπ + ∝, where n ∈ Z (i.e., n = 0, ± 1, ± 2, ± 3,…….)]
⇒ θ = \(\frac{nπ}{3}\)  \(\frac{π}{12}\), where n ∈ Z (i.e., n = 0, ± 1, ± 2, ± 3,…….)
Hence, the general solution of tan 3θ + 1 = 0 is θ = \(\frac{nπ}{3}\)  \(\frac{π}{12}\), where n ∈ Z (i.e., n = 0, ± 1, ± 2, ± 3,…….)
11 and 12 Grade Math
From tan θ = tan ∝ to HOME PAGE
Didn't find what you were looking for? Or want to know more information about Math Only Math. Use this Google Search to find what you need.

New! Comments
Have your say about what you just read! Leave me a comment in the box below. Ask a Question or Answer a Question.